ICE STORAGE CHARACTERISTICS OF FRESH AND BRINED SHARK FILLETS. - SOLANKI, K K; VENKATARAMAN, R (Fishery Technology, 2017)
Ice storage characteristics of fresh and brined fillets from fresh shark (Carcharias melanopterus) were studied in and out of contact with ice for more than two weeks. Changes occurring in biochemical constituents, physical qualities and bacterial counts of the fillets are reported. Shelf life of brined fillets out of contact with ice was considerably longer than that of control samples tinder similar conditions. Icing of shark fillets is suggested as a method for the removal of urea on a commercial scale.